Monitoring dan Evaluasi Daerah Aliran Sungai dengan Penginderaan Jauh dan Sistem Informasi Geografis - Beny Harjadi (Forum Geografi, 2009)
The characteristics of the landcover of a territory were really influenced by the condition biophysical and social his community’s economics. To the territory with the high rainfall had a rare population, the pattern of the landcover was more dominant to the annual crop, conversely to the high rainfall territory had a solid population the pattern of the land cover was more dominant in crops. Whereas to the dry territory (low rain) with the rare inhabitants, the pattern of his land cover was dominated the meadow and the crop kept dry. The requirement would the latest data, the high accuracy, to the area that was wide to monitor the change in one unity of the management of watershed. This research aimed at studying the application of remote sensing (RS) and the geographical information system (GIS) to monitoring and the evaluation of watershed. Physical conditions for the land that was dominated by the land form of the mountainous land and hills with the slope that was steep until precipitous, caused the territory around Grindulu Sub Watershed the potential would the occurrence of the landslide. This landslide incident was also supported by the rock situation that has begun to go mouldy resulting from the disintegration by the hot influence and rain as well as decomposition. Although having some areas of the land that was dominated the bare-rock and the rock-outcrop, but because the land cover was relatively dense in the area of mountains and hills then year round the Grindulu river had not been dry.